La vulneración de los derechos laborales de las Educadoras del CDI Luceritos de la Florencia, del cantón Quito, con el incumplimiento del contrato, durante el año 2021. - Guamarica Guaylla, Gissela Johanna (2022)
The CDI under an agreement between the MIES and outsourcing companies were created in 2013 at the national level, in order to provide a service for the benefit of low-income families, this service consists of the care and stimulation of children under five years. However, in 2019 thre were several irregularities in the agreement signed with the MIES, which caused the salaries of the workers of these centers not to be paid on time, with delays of several months. During the year 2021, even with the uncertainty of Covid 19, the educators of the CDI Luceritos de la Florencia, of the Quito Canton, have had several rights violated in their field of work, one of the main rights violated, the payment of punctual remuneration, which is clearly going against the contract signed by them, being difficult to provide the needs of the home during the time of the pandemic that was being experienced worldwide; Therefore, this topic is of great relevance because it is not only in this CDI that this type of violation of labor rights occurs, but it has become much more frequent at the national level, not only affecting educators, but also to the families that depend on them, this is clearly against the constitution, international treaties and other legal bodies that protect the worker. To obtain first-hand, effective and truthful information, the researcher will carry out surveys and interviews, consequently the respective analysis of the results will be carried out. The researcher with the realization of this project will seek that the labor rights of the educators be respected, that they be paid for the waiting time of their respective salaries, that the days off stipulated by law be fulfilled, improve the work environment by that belong.